Four-Wave Mixing Conversion in QD SOA: reservoir effects - H. Flayyih, Ahmed; H. Ali, Riyam (University of Thi-Qar Journal of Science, 2017)
In this paper, it is present a model to simulate Four-wave mixing in quantum dot semiconductor optical amplifier, taking into account the influence of carrier heating at reservoir. The numerical calculations show that; the carrier heating relaxation at reservoir demonstrates a significant impact on excited state occupation probability, and opposite occurs with ground state. Also, the conversion efficiency is shown a good match with experiment data.